2002
DOI: 10.1509/jmkg.66.3.112.18502
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Search and Use of Nutrition Information: The Challenge and Promise of the Nutrition Labeling and Education Act

Abstract: Four studies investigate the Nutrition Labeling and Education Act's (NLEA's) impact on how consumers use nutrition information. Field and laboratory studies compare, but do not detect any changes in, consumers' search for nutrition information or their recall of this information in the pre-and post-NLEA periods. However, the search activities of a select group (highly motivated and less knowledgeable consumers) benefited more from the NLEA than did other groups. Additional results from the field and lab studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
253
2
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(274 citation statements)
references
References 27 publications
9
253
2
10
Order By: Relevance
“…Regulatory efforts to improve nutritional labeling, such as the 1990 Nutrition Labeling and Education Act (NLEA), have had relatively limited impact in altering the behavior of individuals who were not already motivated to eat more healthily 6,7 . The complexity of processing nutritional information serves to limit the influence of point-ofpurchase labeling 8 , especially in fast-food settings 9 or when many options are available 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulatory efforts to improve nutritional labeling, such as the 1990 Nutrition Labeling and Education Act (NLEA), have had relatively limited impact in altering the behavior of individuals who were not already motivated to eat more healthily 6,7 . The complexity of processing nutritional information serves to limit the influence of point-ofpurchase labeling 8 , especially in fast-food settings 9 or when many options are available 10 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be especially difficult for consumers to interpret a food's contribution to overall diet 11 and to take into consideration the presence of favorable nutrients, given consumers' established tendency to focus disproportionately on avoiding negative components 6,[12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study presents a model, outlined in Figure 1, linking preferences, use of food label information, and comprehension to explore quantitative information processing among younger and older adults. The framework is similar to past models in which use of information and search intensity are important factors of nutrition-related behaviour (Balasubramanian and Cole, 2002;Grunert and Wills, 2007). However, the present model further specifies the role of attention as representing a form of information use and the motivational role of preferences in directing attention to particular types of information.…”
Section: Introductionmentioning
confidence: 92%
“…Associations with nutrition knowledge and NFP numeracy Knowledge has also been shown to be related to food label comprehension across a range of adult ages (Grunert et al, 2010;Misra, 2007;Cowburn and Stockley, 2004;Balasubramanian and Cole, 2002). Li et al (2000) found that knowledge was associated with preferences for %DVs as well as more effective use of %DVs.…”
Section: Processing Of Nfpsmentioning
confidence: 99%
See 1 more Smart Citation